Grading Evaluation of Overall Corrosion Degree of Corroded RC Beams via SMFL Technique. (17th April 2023) - Zhang, Hong; Ma, Xiaotao; Jiang, Hejing; Tong, Kai; Zheng, Yu; Zhou, Jianting
Abstract : To accurately evaluate the overall corrosion degree of reinforced concrete (RC) beams, on the basis of the SMFL technology, the overall random corrosion detection experiment of six RC beams was carried out. The relationship between the tangential component B y and the normal component B z of the magnetic induction intensity and corrosion degree was analyzed, and a multidefect magnetic dipole model was established. The correlation between the average corrosion ratio C of the RC beam and the magnetic characteristic index K G was emphatically explored. The results showed that, with the increase in the average corrosion ratio C, the magnetic characteristic index K G showed an increasing trend as a whole. The index K G could weaken the influence of different historical magnetizations, but it had a certain dispersion. On the basis of the correlation and the Naive Bayesian model, the average corrosion ratio C was divided into four grades. The probability of C falling in different value ranges can be quantitatively evaluated using the K G magnetic characteristic index. The reliability is as high as 97.4% and as low as 56.8% so as to realize the quantitative grading evaluation of the corrosion of the rebar in the RC beam.